Modeling The Relationships Between Export, Import, Inflation, Interest Rate, and Rupiah Exchange - Valentika, Nina; Nursyirwan, Vivi Iswanti; Ilmadi, Ilmadi (Desimal: Jurnal Matematika, 2020)
This research was a modification of research by Catalbas (2016) and Pratikto (2012). The model that can separate long-term and short-term components are the Vector Error Correction Model (VECM). This study aimed to model export, import, inflation, interest rates, and the rupiah exchange rate using VECM and to test the causality between variables using the Granger Causality test. The inter-variable model obtained in this study was VECM with lag 2 using a deterministic trend with the assumption of none intercept no trend and two cointegrations. In export and import, there was an adjustment mechanism from the short-term to the long-term. This research model was appropriate to forecast the export and import where VECM with export and import as the target variables, the cointegration equation (long-run model) for  cointegration equation (long-run model) for Based on the Granger Causality test, it was found that there was a one-way relationship between exchange rates and inflation, export and interest rates, export and import, inflation and export, and import and the interest rate at the significance level of 5%.